The Influence Of Brand Image And Product Quality On Loyalty Through Customer Satisfaction As An Intervening Variable For Customers Of Almeeraakyla Pekanbaru - Permata Putri, Silvi; Syaefulloh , Syaefulloh (Dinasti Publisher, 2024)
The research aims to understand: (1) The influence of brand image on customer loyalty with consumer satisfaction, (2) The influence of product quality on customer loyalty with consumer satisfaction, (3) The influence of brand image on customer loyalty, (4) The influence of product quality on consumer loyalty, and (5) The influence of consumer satisfaction on customer loyalty. The method of this research activity is quantitative. The population in this research activity is consumers who buy and consume Almeeraakayla products in Pekanbaru City with a sample of 100 people. The technique used in analyzing the data is Path analysis. With the results of the research, namely the Brand Image variable (X1) has a positive and significant influence on customer loyalty (Y) through consumer satisfaction (Z). The Product Quality variable (X2) has a positive and significant influence on customer loyalty (Y) through consumer satisfaction (Z). The Brand Image variable (X1) has a positive and significant influence on customer loyalty (Y). The Product Quality variable (X2) has a positive and significant influence on customer loyalty (Y)